Konstruksi identitas nasional melalui konten kreatif: Pengaruh influencer dalam mempromosikan nilai lokal secara internasional - Azis, Mohamad Nur Asrori Abdul (Maliki Interdisciplinary Journal, 2026)
The development of digital media has transformed the way society constructs and expresses national identity. In the era of globalization, influencers and content creators have become important actors in promoting Indonesian local values to global audiences through platforms such as TikTok, Instagram, and YouTube. This study aims to analyze the role of creative content in constructing national identity and the influence of influencers in introducing local culture internationally. The method used is a literature review with a qualitative descriptive approach through the analysis of journals, references, and current digital phenomena. The findings show that influencers act as modern cultural ambassadors who package local values, such as batik, traditional cuisine, regional languages, and customs, into attractive, relevant, and accessible content for young generations and global communities. Authentic creative content can increase national pride, strengthen social cohesion, and enhance Indonesia’s soft power internationally. However, several challenges remain, including cultural commercialization, the dominance of foreign cultures, and limited digital literacy. Therefore, collaboration among government institutions, educational sectors, and creative industries is needed to support sustainable local value-based content production. Thus, creative content becomes a strategic instrument for preserving national identity while improving national competitiveness in the digital era.